Prognostic Role of Invasion-Related Extracellular Matrix Molecules in Diffusely Infiltrating Grade 2 and 3 Astrocytomas - László Szivos; József Virga; Zoltán Mészár; Melinda Rostás; Andrea Bakó; Gábor Zahuczki; Tibor Hortobágyi; Álmos Klekner (Brain Sciences)
Background: Astrocytoma, an IDH-mutant is a common primary brain tumor. Total surgical resection is not feasible due to peritumoral infiltration mediated by extracellular matrix (ECM) molecules. Methods: This study aimed at determining the expression pattern of ECM molecules in different prognostic groups of WHO grade 2 and grade 3 patients and identifying the effect of onco-radiotherapy on tumor cell invasion of grade 3 patients. Gene and protein expression of ECM molecules was determined by qRT-PCR and immunohistochemistry, respectively. Results: In the different prognostic groups of grade 2 tumors HMMR, IDH-1, MKI-67, PDGF-A and versican, in grade 3 tumors integrin α-3, and in both groups integrin α-3 and IDH-1 mRNA expression was significantly different. Regarding protein expression, only integrin αV expression changed significantly in the prognostic groups of grade 2 tumors. Conclusions: Based on the invasion spectrum determined by this joint gene and protein expression analysis, there was a sensitivity of 87.5% and a negative predictive value of 88.9% regarding the different prognostic groups of grade 2 astrocytoma. For grade 3 tumors, the applied standard oncotherapeutic modalities apparently lacked significant anti-invasive effects.